2020
DOI: 10.1177/2042018819897522
|View full text |Cite
|
Sign up to set email alerts
|

Can a modified theory of planned behavior explain the effects of empowerment education for people with type 2 diabetes?

Abstract: Background: The effectiveness of the Patient Empowerment Program (PEP) has been demonstrated in people with diabetes mellitus (DM); however, the underlying reasons for its effectiveness remain unclear. To improve effectiveness, we need to study the psychological mechanism(s) of PEP to understand why it is effective. This study hypothesized that the Theory of Planned Behavior (TPB), modified specifically for people with DM, could describe the mechanism explaining PEP effects. Methods: A longitudinal design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Out of the 3 components of the TPB, social norms and PBC were signi cant in determining the intention to socially distance, while attitude was not a signi cant predictor of intention. These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor.…”
Section: Discussionsupporting
confidence: 92%
“…Out of the 3 components of the TPB, social norms and PBC were signi cant in determining the intention to socially distance, while attitude was not a signi cant predictor of intention. These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor.…”
Section: Discussionsupporting
confidence: 92%
“…Improving the HRQOL of older patients with diabetes is now a great challenge from a public health prospective. Current evidence has indicated that improving medication adherence [33] and selfcare behaviors [34] might be effective. Efforts should be made towards identifying potential meditators such as religious coping and social support in the relationship between diabetes and HRQOL [33].…”
Section: Discussionmentioning
confidence: 99%
“…attitudes, subjective norm, perceived behavioral control, and intention) of TBP. This criticism has led to the inclusion of other related factors [48,49]. Literature shows that affect and emotions can have indirect effects on intentions and behavior independent of the other predictors in the TPB, and that this possibility is not sufficiently accounted for in the TPB [50][51][52].…”
Section: Limitationsmentioning
confidence: 99%